2013
DOI: 10.1590/s0034-71672013000400025
|View full text |Cite
|
Sign up to set email alerts
|

Programa para cuidadores de idosos com demência: relato de experiência

Abstract: This is an experience report on the PRÓ-CUIDEM project, in meetings coordinated by nurse teachers in Niterói-RJ, Brazil. The results are focused on caregivers who need guidance, expressed during the group meetings, where their doubts are clarified, making them feel less anxious and more willing to take care of the elderly, with understanding of the elderly's health problem and, especially, to take care of their own health. One conclude that caring for the elderly with dementia is a difficult task when there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…These adaptive resources can be favored by providing and increasing information on the MND, for example, caregivers can develop new coping strategies for anxiety and stress, for gradual and positive adaptation to the new daily life imposed by care. 29,34,41,46 The preparation of caregivers to perform the task of care may be an ally in the face of the difficulties that caring represents. It should be added that an element to be considered in the dynamics of family care is the preparation of the elderly for important decisions about their possible future care, including the possibility of expressing their preferences regarding the appointment of persons responsible for them, when care performed within the family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These adaptive resources can be favored by providing and increasing information on the MND, for example, caregivers can develop new coping strategies for anxiety and stress, for gradual and positive adaptation to the new daily life imposed by care. 29,34,41,46 The preparation of caregivers to perform the task of care may be an ally in the face of the difficulties that caring represents. It should be added that an element to be considered in the dynamics of family care is the preparation of the elderly for important decisions about their possible future care, including the possibility of expressing their preferences regarding the appointment of persons responsible for them, when care performed within the family.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is of fundamental importance the work of health professionals who will guarantee, in the form of support, information that will have a direct impact on the life of the caregivers and the elderly with MND. 29 The psychological overload of caregivers is perceived to be higher in those with better education, 30 and levels of satisfaction are more related to the personal context and characteristics of the caregiver than to their gender. 31 A clinical trial by Chen et al 32 on the overload of elderly caregivers with MND, indicated the effectiveness of a psychosocial intervention, based on an investigation with two groups of caregivers (with and without intervention).…”
Section: Introductionmentioning
confidence: 99%
“…O homem ao permanecer na concepção técnica do mundo tende a perder-se em seus próprios desejos e medos. Para o cuidador familiar do idoso com DA este fato é agravado pelas situações bizarras e espontâneas advindas do portador, que podem gerar sentimentos de angústia, aflições e perturbações (19) . Este conjunto de situações pode desencadear violência contra o idoso ou contra si próprio, sendo que estes atos violentos são provenientes de momentos de desespero e são prosseguidos do sentimento de culpa.…”
Section: Discussionunclassified
“…[14][15] Considering the main difficulty found by caregivers in explaining how to deal with cognitive disorders of the elderly patients (35/50%), it is evident that the functional deterioration resulting from the disease has vast consequences for the life of the subject and his/her relatives, as it is increasingly necessary to obtain sufficient information about this disease or its treatment for care delivering, as well as deep emotional support. 16 Concrete educational psycho actions can reduce the stress resulting from the impact of the disease, improves the sense of competence and self-esteem of caregivers, reduces anxiety and depressive symptoms, as well as helps to manage emotions and use more effective problem-solving strategies. 17 Dementia, especially at a more advanced stage, causes frequent behavioral disorders such as agitation, excessive ambulation, repetitive speech, verbal and physical aggression that increase stress levels, physical overload, and dissatisfaction to caregivers.…”
Section: The Caregiver and The Care Provided: Particularities And Difmentioning
confidence: 99%